Pengaruh Store Atmosphere Dan Promosi Penjualan Terhadap Keputusan Pembelian Pada Kohwa Coffee House - Alfian Hidayat; Elizabeth Tika Kristina Hartuti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the current era, factors that influence purchasing decisions are one of the crucial things in a business. This is also the focus of Kohwa Coffee House to increase consumer purchasing decisions at Kohwa Coffee House. This study aims to analyze the effect of Store Atmosphere on purchasing decisions at Coffee shop Kohwa Coffe House, to analyze the effect of sales promotion on purchasing decisions at Coffee shop Kohwa Coffee House. And to analyze the effect of Store Atmosphere and sales promotion simultaneously on purchasing decisions at Coffee shop Kohwa Coffee House. The research method used in this research is quantitative method with a sample of 100 people, the data used are secondary data and primary data. The results of this study are Store Atmosphere and sales promotion have a very important role in increasing consumer purchasing decisions at Kohwa Coffee House